2013
DOI: 10.1074/jbc.m112.441089
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast ATP-binding Cassette (ABC) Transporter Ycf1p Enhances the Recruitment of the Soluble SNARE Vam7p to Vacuoles for Efficient Membrane Fusion

Abstract: Background: Ycf1p is a ABCC transporter that is localized to the vacuole and that was initially characterized as a cadmium transporter. Results: Deletion of YCF1 inhibits vacuole fusion in part by excluding the soluble SNARE Vam7p. Conclusion:The vacuole fusion machinery requires Ycf1p function for efficient fusion. Significance: This is the first report that an ABCC protein affects fusion through the recruitment of a SNARE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
(70 reference statements)
0
19
0
Order By: Relevance
“…However, we found that the class C ABC transporter Ycf1 was also needed for Vam7 recruitment. The deletion of YCF1 led to a reduction in vacuolar Vam7 that was linked to inhibited fusion (30). Importantly, the fusion defect observed with ycf1⌬ vacuoles was rescued by …”
Section: The Polybasic Region Of the Vam7 Middle Domain Ismentioning
confidence: 87%
See 2 more Smart Citations
“…However, we found that the class C ABC transporter Ycf1 was also needed for Vam7 recruitment. The deletion of YCF1 led to a reduction in vacuolar Vam7 that was linked to inhibited fusion (30). Importantly, the fusion defect observed with ycf1⌬ vacuoles was rescued by …”
Section: The Polybasic Region Of the Vam7 Middle Domain Ismentioning
confidence: 87%
“…Vacuoles deleted in YCF1 were isolated from RFY32 and RFY33 (30). In vitro content mixing fusion reactions (30 l) contained 3 g each of vacuoles from BJ3505 (PHO8 pep4⌬) and DKY6281 (pho8⌬ PEP4) backgrounds, fusion reaction buffer (20 mM PIPES-KOH, pH 6.8, 200 mM sorbitol, 125 mM KCl, 5 mM MgCl 2 ), ATP regenerating system (1 mM ATP, 0.1 mg/ml creatine kinase, 29 mM creatine phosphate), 10 M coenzyme A, and 283 nM Pbi2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…82 Deletion of Ycf1 caused a significant reduction in fusion efficiency that was linked to the exclusion of Vam7 from isolated ycf1D vacuoles, whereas other SNAREs, HOPS subunits and Ypt7 were uneffected. 83 The attenuated fusion was restored to wild type levels by the addition of recombinant Vam7, indicating that it was able to readily interact with other SNAREs, HOPS and lipids on the membrane to stimulate fusion. Because Vam7 associates with PI3P and Ycf1 might effect the PI3P levels during the fusion reaction we next asked whether the effect of deleting YCF1 on Vam7 recruitment was due to altered PI3P levels.…”
Section: Ycf1 and Fusionmentioning
confidence: 98%
“…S2 in the supplemental material). S. cerevisiae Ycf1p is an ABC transporter that transports a broad range of toxins into vacuoles (33,34). Transcription of A. fumigates abcB can be induced by voriconazole, and the abcB-knockout mutant is hypersensitive to 6 conidia/ml) of the N. crassa WT strain, the ads-4-knockout mutant (⌬ads-4), the ads-4-complemented strain (⌬ads-4::ads-4), and the ads-4 overexpression strain (ads-4 OE ) were spotted onto the center of Vogel's plates (diameter, 9 cm) with or without antifungal drugs.…”
Section: Ads-4 Responds Transcriptionally To Ketoconazole Inmentioning
confidence: 99%